Solidification/stabilization Treatment of Spent Catalyst (V₂O₅) from a Sulfuric Acid Plant using Ordinary Portland Cement (OPC) and an Additive - P1, Agamuthu; L.P, Wong (Malaysian Journal of Science, 2008)
Vanadium pentoxide (V₂O₅) is the most commonly used oxidation catalyst in the production of sulfuric acid. It has a service life of 5 - 10 years and is disposed after its deterioration. Spent catalyst is listed as a scheduled waste under Malaysian Environmental Quality Act (EQA), 1974 and it must be sent to Kualiti Alam Sdn. Bhd. (KA), the only integrated hazardous waste treatment and disposal centre in peninsular Malaysia. Since 2005, an amended regulation allows the spent catalyst to be treated by the waste generator, provided a positive scientific outcome is presented. This paper discusses a scientific study of the spent catalyst treatment using the cement-based solidification/ stabilization (S/S) technique, whereby the treatment effectiveness was investigated through two leaching tests, TCLP and ANS 16.1 (modified). The spent catalyst is a dry, greenish-yellow porous cylindrical solid, which contains mainly silica (56 - 75%). Its metal contents are K (839mg/l), V (356mg/l), Na (99mg/l), Al (44mg/l), Ca (23mg/l), Fe (13mg/l), Mg (13mg/l) and Pb (0.7mg/l). Cement-based S/S was able to control the leaching of the Fe and Pb that exceeded Malaysian EQA wastewater standard limit before the treatment. In addition, leachability index ($L_i$) confirmed that the waste constituents were successfully encapsulated in the solidified matrix. The compressibility of the treated samples was measured using ASTM unconfined compressive strength and proved that they should be able to sustain the load placed on them in a landfill. Tiles and bricks made from the S/S process could potentially be used as construction materials.